Fullmetal alchemist. 06 - Arakawa, Hiromu, 1973- (Viz Media, 2006)
In an alchemical ritual gone wrong, Edward Elric lost his arm and his leg, and his brother Alphonse became nothing but a soul in a suit of armor. Equipped with mechanical "auto-mail: limbs, Edward becomes a state alchemist, seeking the one thing that can restore his brother and himself...the legendary Philosopher's Stone.